RATIONAL USE OF NONSTEROIDAL ANTI-INFLAMMATORY DRUGS. CLINICAL GUIDELINES - A. E. Karateev; E. L. Nasonov; V. T. Ivashkin; A. I. Martynov; N. N. Yakhno; G. P. Arutyunov; L. I. Alekseeva; G. R. Abuzarova; M. A. Evseev; M. L. Kukushkin; S. S. Kopenkin; A. M. Lila; et al. (Научно-практическая ревматология)
In 2015, the experts from various medical associations of Russia elaborated the clinical guidelines “Rational use of nonsteroidal anti-inflammatory drugs (NSAIDs) in clinical practice”. These guidelines were drawn up to improve the use of NSAIDs, our country’s most popular agents to treat pain in acute and chronic diseases. The main purpose of this paper was to reduce the frequency of potentially dangerous class-specific adverse events (AE) that may arise from the use of NSAIDs. To do this, the authors proposed a NSAID choice algorithm based on the assessment of risk factors for AE, the individual characteristics of various representatives of this drug group, and the possibility of prevention of AE.Since then, new data on the efficacy and safety of NSAIDs have been obtained. This has necessitated the revision and addition of a number of provisions in the 2015 guidelines. It seems that the new version of the guidelines, which has been drawn up based on the analysis of a large number of clinical and epidemiological studies, their meta-analysis, by taking into account the clinical experience and opinion of the world’s leading experts, presents more fully the main aspects of the use of NSAIDs in real clinical practice.The guidelines are intended for physicians of all specialties.